Reorganisasi Perusahaan Debitor Yang Terancam Pailit Sebagai Suatu Alternatif - Asril (Faculty of Law, Mulawarman University, 2020)
Law No.37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations Article 2 paragraph (1) has determined that a debtor who has two or more Creditors and does not pay in full at least one debt that has matured and is collectible, is declared bankrupt by verdict Court, either at the request of one or more creditors. With this provision, it can be understood that bankruptcy is a reasonable choice. However, several opinions of bankruptcy law have not provided sufficient protection to debtors with good intentions. This article intends to find out more about the implementation of the reorganization of debtor companies whether it can be used as an alternative so that the debtor company does not go bankrupt. The method used is normative legal research. Data sources consist of primary legal materials, secondary legal materials, and tertiary legal materials. Based on the results of the research, it is known that the regulations regarding company reorganization have not been clearly and firmly regulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations, Reorganization is part of the restructuring, bankruptcy can be avoided through a business reorganization in the form of mergers, consolidations. , business acquisitions, and other forms. This bankruptcy law also does not provide sufficient protection to debtors with good intentions, because there has been a tendency to interpret bankruptcy as liquidation. However, it must be understood that bankruptcy should also be a means of reorganizing the company. The legal consequence of company reorganization on the settlement of the company's debt and accounts receivable is that there is an opportunity for creditors and debtors to settle their debts without going through a bankruptcy process which can result in the debtor being declared bankrupt.